Electrical Simulation of Wind Turbine - ZHANG Jie; DUAN Xulian; ZHANG Xuemei (Kongzhi Yu Xinxi Jishu)
Based on the analysis of stress and coefficient of wind turbine, an approximate expression of power coefficient and output torque were deduced. It discussed simulation method of output characteristics and rotational inertia. Furthermore, simulation of induction machine was carried out for the torque and speed characteristics of wind turbine, and the hardware of the simulation system and the experimental platform were provided. Test results show that the system can not only realize the approximate simulation of output characteristics, but also accurately reflect the effect of rotational inertia on the output characteristics, which offers a convenient testing method to the research of wind power generation.